PENGARUH ENVIRONMENTAL PERFORMANCE PADA ECONOMIC PERFORMANCE DENGAN ENVIRONMENTAL DISCLOSURE SEBAGAI PEMEDIASI (Studi Empiris Pada Perusahaan Manufaktur Dan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia) - Sylvia Christina Daat; Bill J. C. Pangayow (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This research was motivated by the development of the direction of accounting research on green accounting issues. Companies that want a going concern operation must pay attention to 3P, namely profit as profit, people where companies must pay attention to the welfare of the community, and the planet is the company’s contribution to the environment. Therefore, this study tries to find empirical evidence on the influence of several environmental variables, including the environmental performance of the company and disclosure of the company’s environmental management activities to the public on the sustainability of the company with increasing economic (financial) performance of the company. The results of the study using the Structural Equation Model (SEM) approach with the Partial Least Square (PLS) method using Software WarpPLS 5.0 provide empirical evidence that the company’s Environmental Performance influences the company’s Economic Performance, but does not provide empirical evidence that environmental disclosure company as a conncectingvariabel or mediating the relationship of environmental performance with economic performance